Epidemiological and clinical characteristics of childhood pandemic 2009 H1N1 virus infection: an observational cohort study - Rhim, Jung-Woo (BioMed Central, 2011)
BACKGROUND: There was a pandemic influenza around the world in 2009 including South Korea since last pandemic occurred four decades ago. We aimed to evaluate the epidemiological and clinical characteristics of this infection in childhood. METHODS: We evaluated the epidemiologic characteristics of all the subjects infected with the 2009 H1N1 influenza A virus (2,971 patients, ≤ 15 years of age), and the clinical and laboratory findings of the inpatients (217 patients, 80 had pneumonia) between 1 September 2009 and 31 January 2010 in a single hospital throughout the epidemic. RESULTS: The age distribution of all the subjects was relatively even. Over 90% of cases occurred during a two-month period. Two hundred and five patients (94.5%) received oseltamivir within 48 h of fever onset, and 97% of inpatients defervesced within 48 h of medication. The group with pneumonia included more males than females, and had higher leukocytes counts with lower lymphocyte differentials than the group without pneumonia. The white blood cell count and lymphocyte differential were associated with the severity of pneumonia. Corticosteroid treatment for severe pneumonia patients was highly effective in preventing disease progression. CONCLUSION: Children of all ages affected with even rates of infection, but males were predominant in pneumonia patients. Pneumonia patients showed lymphopenia and its severity was associated with the severity of illness. Our results suggest that the mechanism of lung injury in 2009 H1N1 virus infection may be associated with the host immune response.